Maingot's abdominal operations - Maingot, Rodney (McGraw-Hill Medical, 2013)
With each edition, Maingot's Abdominal Operations has built a legacy of expertise,currency, and clinical rigor acclaimed by surgical trainees and practicing surgeons. Presented in full-color for the first time, the 63 streamlined chapters of the twelfth edition offer a concise, yet complete, survey of the diagnosis and management of benign and malignant digestive diseases. This authoritative resource has everything you need to understand congenital, acquired, and neoplastic disorders--and optimize surgical outcomes for any type of abdominal procedure